Knowledge Spillover and Emotional Motivation—A Study on the Willingness and Influencing Factors of Project-Based Learning - Ren, Yanyan (Frontiers in Psychology, 2022)
Project-based learning (PBL) is a task-based learning mode, which is of great significance to the context-based curriculum education. This paper uses questionnaires and interviews to obtain research data, and builds a binary logistic regression analysis model to explore learners’ willingness of PBL and its influencing factors. A total of 14 influencing factors are set, with an innovative import of knowledge spillover and emotional motivation, to examine the impact on PBL willingness. Results show that 8 factors like project-based learning experience, clarity of curriculum tasks, contextuality of curriculum content, requirement for innovation of curriculum tools, etc. have a significant positive impact on learners’ willingness of PBL, while 4 factors, such as challenge of the curriculum project and tendency of learning objectives setting, have a significant negative impact, and the other two examined factors, grade and challenge of the curriculum project, have no significant effects. This paper verifies that individual characteristics, knowledge spillover, and emotional motivation have different directions and degrees of impact on learners’ willingness of PBL, reasons for which are probed into with implications for educators that they should be distinguished and paid due attention to. Finally, suggestions are given in the respect of strengthening the contextuality of curriculum content, identifying the heterogeneity of learners, and expanding innovative tools to develop blended teaching mode. Then, the potential of PBL can be fully realized in maximizing the learning effect.